Fatigue Life Simulation of an Alloy Wheel Design - A. Zakaria, K.; A. Kamarudin, K.; A. Yusuff, M.; B. Ali, M.; Dharmalingam, S. (International Journal of Engineering & Technology, 2018)
Finite element analysis (FEA) is extensively used in the engineering field, especially in structural engineering. FEA is a numerical method used for solving engineering problems that involve complicated geometries, various loading conditions and material properties. A fatigue life assessment of an engineering component is necessary to predict the life span of this component before failure. Automobile alloy wheel is an engineering component that is exposed to fatigue failure in services. Therefore, this study aims to determine the critical area for crack initiation on automobile alloy wheel and to simulate and analyse the fatigue life of an automobile alloy wheel design that is fabricated from different types of materials. The automobile alloy wheel design was modelled using computer-aided design and analysed using commercial finite element software. The automobile alloy wheel was modelled based on a 1200 cc national automobile. Three types of materials, namely, titanium, aluminium and magnesium alloys, were used in this study. A critical part of a steering knuckle could be identified by conducting a stress analysis, and the fatigue life of the automobile alloy wheel could be predicted on the basis of applied loads. Results showed that fatigue life is significantly influenced by the types of material used in a simulation.Â Â